IN VITRO AND OMICS TECHNOLOGIES OPENS A NEW AVENUE FOR DECIPHERING WITHANOLIDE METABOLISM IN WITHANIA SOMNIFERA - Thirugnanasambantham, Pankajavalli; Senthil, Kalaiselvi (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Withania somnifera, commonly known as Ashwagandha or winter cherry, is a principal medicinal plant that has been used in Ayurvedic and native medicine. In view of its varied therapeutic prospective, it has also been the subject of considerable modern scientific attention. Ashwagandha roots are an integral of over 200 formulations in Ayurveda, Siddha and Unani medicine, which are used in the treatment of various physiological disorders. The major chemical constituents of this plant, the withanolides, are a group of naturally occurring C28-steroidal lactones. It has been extensively investigated in terms of chemistry and bioactivity profiling. However, there exists only very little fragmentary evidence about the dynamics of withanolide biosynthesis. This review examines different in vitro approaches that had been carried out over past decade of years and newly developed omics technologies for the large scale production of withanolides as well as for the analysis of genes associated with withanolide biosynthesis. Keywords: Withania somnifera, Withanolides, in vitro cultures, Genomics, Transcriptomics, In silico, Proteomics, Metabolomics.